Prenatal Events and CNS Migration Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The role of pre-, peri-, and postnatal environmental factors and genetic predisposition in the genesis of neuronal migration disorders (NMD) in 40 patients with epilepsy was determined by standardized questionnaires at the Montreal Neurological Institute and Hospital, Canada.